Inclusion of Essential Universal Health Coverage Services in Essential Packages of Health Services: A Review of 45 Low- and Lower- Middle Income Countries. Issue 1 (1st January 2022) - Shekh Mohamed, Idil; Hepburn, Jasmine Sprague; Ekman, Björn; Sundewall, Jesper
ABSTRACT: Expanding service coverage and achieving universal health coverage (UHC) is a priority for many low- and middle-income countries. Though UHC is a long-term goal, its importance and relevance have only increased since the start of the COVID-19 pandemic. The first step on the road to UHC is to define and develop essential packages of health services (EPHSs), a list of clinical and public health services that a government has deemed a priority and is to provide. However, the nature of these lists of services in low- and lower-middle-income countries is largely unknown. This study examines the contents of 45 countries' EPHSs to determine the inclusion of essential UHC (EUHC) services as defined by the Disease Control Priorities, which comprises 21 specific essential packages of interventions. EPHSs were collected from publicly available sources and their contents were analyzed in two stages, firstly, to determine the level of specificity and detail of the content of EPHSs and, secondly, to determine which essential UHC services were included. Findings show that there are large variations in the level of specificity among EPHSs and that though EUHC services are included to a large extent, variations exist regarding which services are included between countries. The results provide an overview of how countries are designing EPHSs as a policy tool and are progressing toward providing a full range of EUHC services. Additionally, the study introduces new tools and methods for UHC policy analysts and researchers to study the contents of EPHSs in future investigations.